A Study of Investment Behavior of Millennial’s in Pune City - Patil, Ms.Vaishali Rajendra; Mali, Dr. Nitin (The journal of contemporary issues in business and government, 2021)
Millennial play very important role in financial sector of the economy. All millennials are bound to disrupt,reshape & recounter the economy. The factor which influence on investment decisions of millennials are financial knowledge, age, income, gender, rate of return, risk involved in investment, objective of investment. In this research, researcher has studied the investment behavior of millennials in Pune City, factors influencing the investment decisions, Pattern of investment and problems faced by the millennials while investing. The current study reveals that there is no significant association exists in age and Investment Avenue. Association between income and investment pattern are low degree negatively correlated. If income increases then investment pattern falling down, however this proportion is marginal. Therefore the significant association not revealed by the hypothesis testing. The study found that financial knowledge is positively correlates with investment behavior.